2016
DOI: 10.1080/08929882.2016.1184531
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Breeding Blankets Using Antineutrinos

Abstract: The Plutonium Management and Disposition Agreement between the United States and Russia makes arrangements for the disposal of 34 metric tons of excess weapon-grade plutonium. Under this agreement Russia plans to dispose of its excess stocks by processing the plutonium into fuel for fast breeder reactors. To meet the disposition requirements this fuel would be burned while the fast reactors are run as burners, i.e., without a natural uranium blanket that can be used to breed plutonium surrounding the core. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Beyond the realm of traditional safeguards, RETINA-type systems have also been proposed for disarmament negotiations and plutonium disposition. A recent study has argued for their deployment in Russian fast reactors tasked with eliminating plutonium stockpiles 29 . Studies have also investigated how they can be used to monitor MOX burnup in a PWR to verify plutonium incineration 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the realm of traditional safeguards, RETINA-type systems have also been proposed for disarmament negotiations and plutonium disposition. A recent study has argued for their deployment in Russian fast reactors tasked with eliminating plutonium stockpiles 29 . Studies have also investigated how they can be used to monitor MOX burnup in a PWR to verify plutonium incineration 30 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible to detect them in CEνNS detectors. A detailed study has been performed (Cogswell and Huber, 2016) and the authors found that detectors of moderate size, several tens of kilograms, could reliably detect the presence of a breeding blanket.…”
Section: B Neutrino-based Approachesmentioning
confidence: 99%
“…Recent work has shown that neutrino detectors, both using IBD (i.e.ν e capture on free protons) and CEνNS on nuclei, can serve as novel state of the art instruments for monitoring nuclear facilities (see [227] for a review). This includes both civilian nuclear reactors, where precise measurements of theν e flux can provide information about spent fuel [228,229], and the global excess of fissile nuclear materials [230,231]. These ideas have already motivated the construction of one such neutrino-based nuclear reactor monitoring system [232].…”
Section: Nuclear Facility Monitoringmentioning
confidence: 99%
“…In both cases, CEνNS occupies a unique and complementary position relative to IBD because of its thresholdless nature [231,233]. There are two ways in which CEνNS differentiates itself from IBD.…”
Section: Nuclear Facility Monitoringmentioning
confidence: 99%
See 1 more Smart Citation